Financial Performance Analysis using Economic Value Added (EVA) Method at PT. Darma Henwa Tbk. Period 2017-2019 - Abdul Muta Ali; Adi Saputro; Muhammad Fahmi Nurani; Marliza Noor Hayatie (International Journal of Research in Vocational Studies (IJRVOCAS), 2021)
Measurement of financial performance is the achievement of the company's achievements in a period that describes the financial health condition of the company. This study aims to determine the calculation and measurement of the financial performance of PT financial statements. Darma Henwa Tbk in 2017-2019. Analysis in this study using Economic Value Added (EVA) method. The results of research on PT. Darma Henwa Tbk. shows that 2017 with a value of $199,460 shows a positive value. This is because the value of NOPAT in that year is greater than the capital charge value generated. Meanwhile, in 2018 the value of EVA increased by $2,893,767, which still generated positive value in that year. However, in 2019 EVA value decreased and obtained a negative value of -$764,780. The decrease is caused because the value of NOPAT in 2019 is smaller than the capital charge value.